Fabrication and characterisation of substrate-free PZT thick films. Issue 12 (15th August 2018) - Wang, Dazhi; Shi, Peng; Li, Xuemu; Zhou, Peng; Zhao, Kuipeng; Wei, Yunlong; Jiang, Chongyang; Liang, Junsheng; Dorey, R.A.
Abstract: This paper reports the preparation of dense and substrate-free PZT thick films. Electrohydrodynamic jet deposition and sol infiltration were utilized to produce dense PZT thick film, then wet chemical etching was employed to successfully remove the silicon substrate. Subsequently, a pure PZT thick film having a thickness of 14 µm without substrate was produced. The piezoresponse force microscopy technique was used to examine the piezoelectric constant ( d 33, f ), it was found that the d 33 was increased from 71 pm V −1 to 140 pm V −1, having a double increase. It was also observed that the remnant polarization ( P r ) and relative permittivity ( ε r ) of PZT film were distinctly improved after the removal of silicon substrate. The experimental result shows that the substrate clamping had great effects on the electrical properties of PZT films and its effect value was evaluated. In addition, the systematic theoretical analysis of the substrate clamping on film was deeply studied. The theoretical analysis agrees well with the experiment results, which can be used to estimate the effect value caused by the substrate clamping.